Mis-Measuring Our Universities: Why Global University Rankings Don’t Add Up - Gadd, Elizabeth (Frontiers in Research Metrics and Analytics, 2021)
Draws parallels between the problematic use of GDP to evaluate economic success with the use of global university rankings to evaluate university success. Inspired by Kate Raworth’s Doughnut Economics, this perspective argues that the pursuit of growth as measured by such indicators creates universities that ‘grow’ up the rankings rather than those which ‘thrive’ or ‘mature’. Such growth creates academic wealth divides within and between countries, despite the direction of growth as inspired by the rankings not truly reflecting universities’ critical purpose or contribution. Highlights the incompatibility between universities’ alignment with socially responsible practices and continued engagement with socially irresponsible ranking practices. Proposes four possible ways of engendering change in the university rankings space. Concludes by calling on leaders of ‘world-leading’ universities to join together to ‘lead the world’ in challenging global university rankings, and to set their own standards for thriving and maturing universities.